Identify Inflammatory Bowel Disease-Related Genes Based on Machine Learning - Ye, Lili; Lin, Yongwei; Fan, Xing-di; Chen, Yaoming; Deng, Zengli; Yang, Qian; Lei, Xiaotian; Mao, Jizong; Cui, Chunhui (Frontiers in Cell and Developmental Biology, 2021)
The patients of Inflammatory bowel disease (IBD) are increasing worldwide. IBD has the characteristics of recurring and difficult to cure, and it is also one of the high-risk factors for colorectal cancer. The occurrence of IBD is closely related to genetic factors, which prompted us to identify IBD-related genes. Based on the hypothesis that similar diseases are related to similar genes, we purposed a SVM-based method to identify IBD-related genes by disease similarities and gene interactions. 135 diseases which have similarities with IBD and their related genes were obtained. These genes are considered as the candidates of IBD-related genes. We extracted features of each gene and implemented SVM to identify the probability that it is related to IBD. 10-cross validation was applied to verify the effectiveness of our method. We prioritized the candidate genes and did case studies on top five genes.